Establishing a national linked database for Fetal Alcohol Spectrum Disorder (FASD) in the UK: multi-method public and professional involvement to determine acceptability and feasibility - Harding, Sarah; Samways, Beverley; Dillon, Amy; Butcher, Sandra; Boyd, Andy; Mukherjee, Raja; Cook, Penny; McQuire, Cheryl (International Journal of Population Data Science, 2024)
Introduction Fetal Alcohol Spectrum Disorder (FASD) is one of the leading non-genetic causes of developmental disability worldwide and is thought to be particularly common in the UK. Despite this, there is a lack of data on FASD in the UK. Objective To conduct public and professional involvement work to establish stakeholder views on the feasibility, acceptability, key purposes, and design of a national linked longitudinal research database for FASD in the UK. Methods We consulted with stakeholders using online workshops (one for adults with FASD [and their supporters] N\,$=$\,5; one for caregivers of people with FASD (N=7), 1:1/small-team video calls/email communication with clinicians, policymakers, data-governance experts, third-sector representatives, and researchers [N=35]), and one hybrid clinical workshop (N\,$=$\,17). Discussions covered data availability, benefits, challenges, and design preferences for a national pseudonymised linked database for FASD. We derived key themes from the notes and recordings collected across all involvement activities. Results Our tailored, multi-method approach generated high levels of stakeholder engagement. Stakeholders expressed support for a pseudonymised national linked database for FASD. Key anticipated benefits were the potential for: increased awareness and understanding of FASD leading to better support; new insights into clinical profiles leading to greater diagnostic efficiency; facilitating international collaboration; and increased knowledge of the long-term impacts of FASD on health, social care, education, economic and criminal justice outcomes. Given the rich data infrastructure established in the UK, stakeholders expressed that a national linked FASD database could be world-leading. Common stakeholder concerns were around privacy and data-sharing and the importance of retaining space for clinical judgement alongside insights gained from quantitative analyses. Conclusions Multi-method and multidisciplinary public and professional involvement activities demonstrated support for a national linked database for FASD in the UK. Flexible, diverse, embedded stakeholder collaboration will be essential as we establish this database.